Impact of Terrorism in the process of Industrial Development: A study on the Tea Industry of Assam - Hazarika, Dr. Kakali (IJRDO - Journal of Social Science and Humanities Research, 2017)
Terrorism means the use of extreme public violence to achieve a particular goal or to force someone to do something. Basically terrorists attempt to create political and social change by threatening the welfare of their opponents. North East India has immense potentialities for industrial development being covered with international border. It is enriched with a large bucket of natural resources, wide open spaces and the power of a huge manpower. But it lacks the basic component for industrial development i.e. foreign investment. One of the basic causes of this leakage is insurgency or terrorist problems. Investors have a fear of losing their money or even their lives. The incidence of kidnapping or killing business persons, entrepreneurs, land lords etc. by terrorist create a deep fear in the minds of outsiders. Among the tea producing states of India, Assam is well known internationally since long back. The state is continuously dominating the country’s tea map by producing almost half of country’s total tea production. It has the potentiality for making a positive economic impact ensuring new employment opportunities, proper utilization of local resources and source of revenue. Tea industry, one of the major sources of revenue and employment generator of India as well as Assam is also suffering from this terrorist problem. Kidnapping or killing of tea garden owner and managers is burning news in news channels and papers. Moreover; conflict between labour and management is also a common issue in tea gardens. In these contexts this paper will highlight the impacts of terrorism on the tea industry of Assam and measures to overcome the problems.